ASTM designation E1625-94 : Standard test method for determining biodegradability of organic chemicals in semi-continuous activated sludge (SCAS). (West Conshohocken (Pa.) : ASTM International)
1.1 This test method covers procedures for the determination of the biodegradability or removability, or both, of nonvolatile organic chemicals (Henry's Constant <10 -3 atm/m3 /day) using a laboratory bench scale test and activated sludge from a domestic wastewater treatment plant. 1.2 This test method is derived from a procedure developed for surfactants by the Soap and Detergent Association (1, 2), one developed for alkylbenzene sulfonates by ASTM (see Test Method D2667) and one developed by the Organization for Economic Cooperation and Development (OECD) for assessing inherent biodegradation (3) and also codified in the Toxic Substances Control Act Test Guidelines (4). For assessment of variability, replicate test systems (three or more) should be employed. It is recommended that the tests be used for chemical compounds that can be well characterized with respect to chemical and physical properties. Testing of mixtures or fully formulated products can lead to serious problems in
Data interpretations. 1.3 The procedures involve the exposure of the test chemical(s) to activated sludge mixed liquor microorganisms over a finite time cycle in specially designed aeration chambers. Biodegradability is determined from dissolved organic carbon (DOC) measurements, from radiochemical analyses, or from measurements of test chemical concentration using a specific analytical method. Based on DOC analyses alone, biodegradation can only be claimed if other removal mechanisms (for example, adsorption, volatility, or chemical transformation) are discounted by means of specific testing or knowledge of physical chemical properties of the test chemical. Modifications of this test method for water insoluble and moderately volatile chemicals are presented in this test method and principles are described in somewhat more detail elsewhere (see 5, 6). 1.4 These procedures may also be used as a means of acclimating microorganisms to an organic chemical over an extended period. The acclimated
Microorganisms may be used as an inoculum source for other biodegradation tests.
Keywords: Normen